CP-MLR Directed QSAR Rationales for the 1-aryl Sulfonyl Tryptamines as 5-HT6 Receptor Ligands: An Advanced Study - Choudhary, Manju; Deshpande, Shreekant; Sharma, Brij Kishore (Technological Innovation in Pharmaceutical Research Vol. 7, 2021)
A QSAR study has been carried out to rationalize the 5-HT6 receptor binding affinities of the 1-aryl sulfonyl tryptamine derivatives using Dragon descriptors. A higher value of molecular symmetry and topology accounting Randic shape index descriptor PW4 (path/walk 4) would be favorable to improve the binding affinity. Presence of more number of bromine atoms (descriptor nBR) and presence of such structural fragment in which a hydrogen atom attached to sp3 hybridized carbon with no hetero atom rather than one hetero atom attached to next carbon atom (descriptors H-046 and H-052) will be supportive to the activity. The prevalence of atomic properties to explain the binding affinity is evident from the associations of polarizability to the path length 7 of Moran autocorrelation (MATS7p), masses to eigenvalues n.2 and 7 of Burden m atrix (BELm2 and BEHm7), Sanderson electronegativity to highest eigenvalue n.2 Burden matrix (BEHe2) and van der Waals volume to path length 8 of Geary autocorrelation (GATS8v) and charge content in terms of topological and mean topological charge indices (GGI3 and JGI2). The dominance of the information content of the descriptors, emerged in CP-MLR models, has also confirmed by the PLS analysis. The derived QSAR models and descriptors shared in these models revealed that the substituents of tryptamine moiety have sufficient scope for further modification. The present study has provided structure–activity relationships of the binding affinities of tryptamine derivatives to 5-HT6 receptor in terms of structural requirements